ISOLASI GLUKOMANAN DARI DUA JENIS ARACEAE: TALAS {Colocasia esculenta (L.) Schott} DAN Iles-iles (Amorphophallus campanulatus Blumei) - Chairul Chairul; Sofnie M Chairul (BERITA BIOLOGI, 2006)
Talas {Colocasia esculenta (L.) Schott} and Iles-iles (Amorphophalus campanulatus Blumei) have been used as source of carbohydrate especially in tropical regions, mainly in East Indonesia. Talas and iles-iles, that contains carbohydrate and several substances for instance glucomannan would form viscous liquid and were used as emulgator, capsule cosmetics and dietary.The research was conducted to separate glucomannan from starch of talas and iles-iles fresh and dry (powder).The methods base on speed of revolution (centrifuge) in 5000 to 19000 rpm and the duration of rotation was 10 to 40 minutes and the filtrate was precipitated by using several alcohols (methanol, ethanol, propanol, isopropanol and isobutanol). The results showed that speed of rotation 17 x 1000 rpm with 10 minutes rotation resulted in good glucomannan separation from starch.Ethanol and isopropanol were the best solvent to separate glucomanan from dissolved starch in the filtrate with ratio 2 : 3 and for dry material, and the maximal agitation reached after 2 hours. Glucomannan content on fresh material was higher than as in talas (4.08 %) and iles-iles (5.64 %), compared to these in powder (dried) of talas (3.87 %) and iles-iles (5.41 %). The purerity of isolated glucomannan was higher compared to control.